FILSAFAT PENDIDIKAN ISLAM DAN SIKAP MAHASISWA PGSD TERHADAP ISU KONFLIK KEMANUSIAAN DI TIMUR TENGAH (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic education plays a strategic role in shaping students' social awareness, not merely as a medium for religious knowledge transfer, but also as a foundation for character development and humanitarian concern. This study examines the relationship between students' understanding of Islamic educational philosophy values and the attitudes of Elementary School Teacher Education (PGSD) students in responding to humanitarian conflict issues in the Middle East, particularly Palestine. A qualitative library research method was employed, utilizing content analysis and hermeneutical interpretation across relevant literature sources. The findings reveal that students' comprehension of values such as 'adl (justice), rahmah (compassion), and musawah (equality) remains predominantly at the cognitive-normative level and has not yet transformed into consistent affective attitudes. This gap between knowledge and attitude indicates that the value internalization process within Islamic higher education practices remains suboptimal. Therefore, educational institutions need to design curricula that are more contextual, participatory, and integrative, so that students' humanitarian awareness can be authentically cultivated as an integral part of their professional identity as